Applied Probability and Statistics - Lefebvre, Mario (Springer New York : Imprint: Springer, 2006)
This text is designed for a one-semester course on Probability and Statistics. The exposition unfolds systematically from an introductory chapter to such topics as random variables and vectors, stochastic processes, estimation, testing and regression. The topics are well chosen and the presentation is enriched by many examples from real life. Following every chapter, the reader will find many original, solved and unsolved problems and hundreds of multiple choice questions, enabling those unfamiliar with the topics to master them. Additionally appealing are the interesting historical notes on the mathematicians mentioned throughout and a useful bibliography. A distinguishing character of the book is the thorough and succinct handling of the various topics. This book assumes a basic knowledge of differential and integral calculus. Whether in a classroom setting or for self-study, this textbook will benefit students in applied mathematics, engineering, computer science and in the applied sciences in general. A separate solutions manual is available to instructors.